Hadith Review: The Validity of Ablution for Women Who Wear Waterproof Henna - Ilmiyah, Dakhirotul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study analyzes the validity of ablution for women who use waterproof henna. Wudhu, as one of the main forms of worship in Islam, requires perfection in its execution, including ensuring water can reach all the required body parts. The emergence of waterproof cosmetics such as henna has triggered questions regarding the validity of wudhu for its users. This research uses a qualitative approach with a literature study method that focuses on analyzing the matan of the hadith. The criteria of matan validity based on the perspective of scholars such as Muhammad al-Ghazali and Subhi Sholih form the basis of this research. The results show that waterproof henna can prevent ablution water from reaching the skin, making ablution invalid. Therefore, users of waterproof henna need to ensure that the material has been cleaned before wudhu. This study also provides theoretical and practical insights for Muslim women as well as scholars to understand the correct ablution procedure according to Islamic law. The study recommends practical steps in addressing the use of waterproof cosmetics to maintain the validity of worship.